The effect of oxidant and salt levels on the functional properties and cost-effectiveness of open-top standard white bread for the baking industry - Vorster, Sanetta Henrietta (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Home Economics) -- University of Stellenbosch, 1993.